Vaso-nervorumitis: responsible for pain in Buerger’s disease? - Fazeli, Bahare (Int Med Case Rep J, 2019)
Buerger’s disease (BD) is an episodic, inflammatory, and occlusive peripheral vascular disease with unknown etiology, which can lead to tissue or limb loss. BD patients usually present neurological symptoms from the early stages of the disease including numbness, cold sensation, and allodynia as the disease progresses. Pain in the late stages of BD is very severe, almost resistant to opioid pain killers, and sometimes compels the patient to pursue major amputation. Therefore, pain management in BD patients is one of the most important and, at the same time, challenging issues since its main etiology is not well understood. Recently, a 39-year-old male smoker with a diagnosis of BD underwent a below-knee amputation in his left leg. Oddly, we found that the vasa-nervorum of the sural nerve had the pathological changes usually observed in BD, including inflammation and proliferation of endothelial cells. Notably, the inflammation was limited to the vasa-nervorum and did not extend to the nerve fascicles. Our findings could provide a clue to taking the approach of managing pain in BD as if it were vasculitis neuropathy; and the inflammation of the vasa-nervorum individually might be responsible for the pain characteristic of BD. In addition, our findings could indicate that BD is a systemic vasculitis of microcirculation and, hence, a different treatment approach for BD might be needed in addition to antithrombotic and vasodilator.